The Short- and Long-Term Effects of Family-Friendly Policies on Mothers' Employment - Alicia De Quinto; Libertad González (Institute of Labor Economics (IZA), 2024)
Countries often encourage part-time work among new parents as part of their family policies, aiming to foster mothers' labor market attachment. However, this approach may unintentionally impede women's long-term career prospects. We examine the impact of a 1999 Spanish reform that allowed parents to reduce their working hours by up to a half while their youngest child was under age 6, along with job protection measures. Leveraging eligibility rules, we follow a regression kink design, comparing ineligible women to mothers who had varying lengths of eligibility, and tracking their subsequent work trajectories. Our findings show that longer eligibility led to a modest increase in maternal part-time work during her child's early years, with mothers working approximately one additional day part-time for each extra month of eligibility. This increase in part-time work substituted for days spent in unemployment rather than reducing full-time work, leading to a rise in earnings. In the long term, extended eligibility also led to improvements in both employment and earnings. Overall, we find that the policy had a positive impact on the labor supply and earnings of women with children, both in the short and long term.
Keywords: J08; J13; J16; J18; 330; worktime reduction; maternity; childcare policies